Serum levels of bone turnover markers including calculation of Z-scores: Data from a Dutch healthy reference cohort - Mark Siderius; Suzanne Arends; Anneke Muller Kobold; Lucie Wagenmakers; Karin Koerts; Anneke Spoorenberg; Eveline van der Veer (Bone Reports, 2023)
Introduction: Bone turnover markers (BTM) are biochemical compounds reflecting different stages of bone metabolism. Their levels change with age and differ between males and females. This makes clinical interpretation and comparison more difficult. Therefore, our aim was to establish BTM reference values which can be used to calculate Z-scores for use in daily clinical practice. Methods: Serum markers of collagen resorption, bone formation/regulation, collagen formation and bone mineralization (sCTX, OC, PINP and BALP, respectively) were measured in non-fasting volunteers without bone-related abnormalities. Raw data was plotted and gender-specific age cohorts were established with their respective means and standard deviations (SD). Z-scores can be calculated using these reference values to correct for the influence of age and gender on BTM. Results: In total, 856 individuals were included of which 486 (57 %) were female. Individuals were aged between 7 and 70 years. Highest serum levels of BTM were found in childhood and puberty. Peak levels are higher in boys than girls and prevail at later ages. In adults, BTM levels decrease before reaching stable nadir levels. In adults, 10-year reference cohorts with means and SD were provided to calculate Z-scores. Conclusion: With our data, Z-scores of sCTX, OC, PINP and BALP can be calculated using reference categories (for age and gender) of Caucasian healthy volunteers. Clinicians can use BTM Z-scores to determine whether there are changes in bone turnover physiology beyond those expected during aging. BTM Z-scores facilitate harmonization of data interpretation in daily clinical practice and research.